TRANSLANGUAGING AND IDENTITIES CONSTRUCTIONS: INVESTIGATING MULTILINGUAL PRACTICES AMONG INDONESIAN ENGLISH LEARNERS IN A UNIVERSITY - Fauziyah, Nur Nabilah; Andriani, Merry (Premise: Journal of English Education and Applied Linguistics, 2025)
This article examines the impact of translanguaging spaces on the language practices and identity constructions of Indonesian English learners. To answer these questions, we employed multiple conceptual frameworks, including the concept of translanguaging, moment analysis, and English global positions. We collected the data through classroom observation, semi-structured interviews, and an analysis of written texts from fifth-semester students in the English Literature department at an Indonesian university in Malang. The findings show that translanguaging is highly appreciated by most Indonesian English learners, both in oral presentations and written works. Translanguaging has several pedagogical functions, including improving students' understanding of content, clarifying complex ideas, providing authenticity to stories, and reducing language anxiety. We also found multiple and dynamic identities constructed by participants in different contexts, namely hybrid identity, multilingual identity, laissez-faire liberalism, colonial celebration, and linguistic imperialism. These dynamic identities are primarily influenced by the dominance of monolingual and colonial celebration views in various contexts, despite the increasing use of translanguaging in classrooms.